Conformality for a robust class of non-conformal attractors - Pozzetti, Maria Beatrice; Sambarino, Andrés; Wienhard, Anna (Arxiv, 2019)
In this paper we investigate the Hausdorff dimension of limit sets of Anosov representations. In this context we revisit and extend the framework of hyperconvex representations and establish a convergence property for them, analogue to a differentiability property. As an application of this convergence, we prove that the Hausdorff dimension of the limit set of a hyperconvex representation is equal to a suitably chosen critical exponent. In the appendix, in collaboration with M. Bridgeman, we extend a classical result on the Hessian of the Hausdorff dimension on purely imaginary directions.
Gesehen am 11.02.2019